Penerapan Manajemen Pembelajaran Daring di Sekolah Menengah Pertama Negeri Karang Jaya Musi Rawas Utara - Yanto, Murni; Zulaiha, Siti (Pascasarjana IAIN Kudus, 2022)
The purpose of this study is to find out how the implementation of online learning at karang jaya Musi Rawas utara Junior High School which carried out online learning during covid-19 pandemic. This type of research is qualitative. Implementation of online learning at Karang Jaya Musi Rawas Utara Junior high school :(a) educators use a strategy of utilizing teaching time, then teachers also provide reinforcement and enrichment using online media (b) the teaching method used is collaboration between face-to-face learning and teaching methods online learning (c) the learning media used are electronic media and the used of online based aplications such as WhatApp,Google Meet and Zoom. (d)evaluation of online learning which carried out.